2012
DOI: 10.3747/co.19.1149
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers That Currently Affect Clinical Practice: EGFR, ALK, MET, KRAS

Abstract: New drugs such as pemetrexed, the epidermal growth factor receptor (egfr) tyrosine kinase inhibitors, and the Alk inhibitor crizotinib have recently enabled progress in the management of advanced non-smallcell lung cancer (nsclc). More drugs, especially Met inhibitors, will follow. However, the benefits of these agents are not uniform across the spectrum of nsclc, and optimizing their utility requires some degree of subgrouping of nsclc by the presence or absence of certain biomarkers.The biomarkers of current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…Low-level differential expression of ALK protein means that careful optimization of antibody clone and detection system is required [52]. A number of antibodies are now in development, and IHC may become a standard of care diagnostic (potentially with augmentation) [53,59]. There is also some clinical evidence to suggest that diagnosis based on FISH only may less accurately predict response to crizotinib than combined FISH/IHC/RT-PCR (ORR 81% for patients diagnosed based on combined tests vs 48% for patients diagnosed by FISH only; p=0.007) [60].…”
Section: Current Pathologic and Molecular Testing Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-level differential expression of ALK protein means that careful optimization of antibody clone and detection system is required [52]. A number of antibodies are now in development, and IHC may become a standard of care diagnostic (potentially with augmentation) [53,59]. There is also some clinical evidence to suggest that diagnosis based on FISH only may less accurately predict response to crizotinib than combined FISH/IHC/RT-PCR (ORR 81% for patients diagnosed based on combined tests vs 48% for patients diagnosed by FISH only; p=0.007) [60].…”
Section: Current Pathologic and Molecular Testing Guidelinesmentioning
confidence: 99%
“…For example, although FISH is the FDA-approved clinical standard that detects all variants and is suitable for FFPE specimens [52,53], not all patients with NSCLC who may benefit from ALK inhibitor treatment are identified [54][55][56]. FISH has a number of disadvantages, being both more time-consuming and technically demanding than some other methods, with variability among observers, and scoring complications [52][53]57]. By contrast, IHC is a less time-consuming [58], relatively simple and widely available procedure [52].…”
Section: Current Pathologic and Molecular Testing Guidelinesmentioning
confidence: 99%
“…As mutation testing expands to include new targets including human epidermal growth factor receptor 2 ( HER2 ), BRAF, RET and MET and effective treatments are found, the treatment algorithms will increase in complexity (3). …”
Section: Introductionmentioning
confidence: 99%
“…We believe that the co-development of new drugs with companion diagnostics will govern the progress in oncology in the immediate future. The role of companion biomarkers in guiding treatment in patients with cancer has been recently very nicely reviewed (Duffy and Crown 2013;Ong et al 2012;Vincent et al 2012) (Table 3).…”
Section: Dna Mutations In Cfdna As Companion Diagnostic Lung Cancer Bmentioning
confidence: 99%
“…EGFR mutations may also have indirect value as predictors of sensitivity to chemotherapy and to radiotherapy and molecularly targeted agents (Vincent et al 2012). Murtaza et al have recently identified in plasma an increased representation of a resistance-conferring mutation in EGFR following treatment with gefitinib in association with the emergence of therapy resistance.…”
Section: Dna Mutations In Cfdna As Companion Diagnostic Lung Cancer Bmentioning
confidence: 99%